Influence of Project Staff on Sustainability of Early Childhood Development Projects: Case of Baby-Friendly Community Initiative in Dagoretti North Constituency Nairobi County, Kenya - Obulemire, Kepha; Sagwa, Evans (Journal of Human Resource and Leadership, 2025)
Purpose: The aim of the study was to examine the influence of project staff on sustainability of Early Childhood Development (ECD) projects, a case of the Baby-Friendly Community Initiative (BFCI) project in Dagoretti North Constituency Nairobi County, Kenya. Methodology: The study adopted a descriptive survey design. The target population was made up of 507 BFCI project stakeholders while the sample size was 211. The target population comprised five hundred project beneficiaries, two lead mothers in charge of the mother-to-mother groups, two government officials, two Ministry of Health staff, and one staff from the implementing partner of the project. The sample size of the project beneficiaries was derived using the Yamane formula. Stratified sampling was used to get study participants from each village representing a stratum. Proportionate stratification was used to get the sample size of each stratum. This meant that each stratum had the same sampling fraction. The other study participants were not sampled due to their low number. The use of descriptive survey design helped in obtaining data from a large number of participants who took part in the study. The researchers used self-administered questionnaires to collect quantitative data while an interview guide was used to collect qualitative data in the research. Percentages, frequencies, mean, and standard deviation were the descriptive statistics used while correlation analysis was used for inferential statistics. Data collected from the study was analyzed with the help of the Statistical Package for Social Sciences (SPSS Version 23.0) and triangulated qualitative data was analyzed through themes and content analysis. Findings: The study found out that the relationship between project staffing and sustainability had a moderate correlation value of (r=0.428, P<0.000). The study found out that project staff contribute to the sustainability of projects if they are supported to develop their skills, are appreciated where they work and are involved in decision making. Unique Contribution to Theory, Practice and Policy: The study recommends that the recruitment of staff should be objectively carried out so as to get competent and highly qualified staff who will contribute to the sustainability of the project. Project stakeholders need to use transparent recruitment processes when hiring project staff to avoid discontentment that can sabotage the sustainability of a project. The study recommends for studies to be conducted to look at other age groups that are not ECD projects.